Adaptive pathways and emerging strategies overcoming treatment resistance in castration resistant prostate cancer - Cameron M. Armstrong; Allen C. Gao (Asian Journal of Urology)
The therapies available for prostate cancer patients whom progress from hormone-sensitive to castration resistant prostate cancer include both systemic drugs, including docetaxel and cabazitaxel, and drugs that inhibit androgen signaling such as enzalutamide and abiraterone. Unfortunately, it is estimated that up to 30% of patients have primary resistance to these treatments and over time even those who initially respond to therapy will eventually develop resistance and their disease will continue to progress regardless of the presence of the drug. Determining the mechanisms involved in the development of resistance to these therapies has been the area of intense study and several adaptive pathways have been uncovered. Androgen receptor (AR) mutations, expression of AR-V7 (or other constitutively active androgen receptor variants), intracrine androgen production and overexpression of androgen synthesis enzymes such as Aldo-Keto Reductase Family 1, Member C3 (AKR1C3) are among the many mechanisms associated with resistance to anti-androgens. In regards to the taxanes, one of the key contributors to drug resistance is increased drug efflux through ATP Binding Cassette Subfamily B Member 1 (ABCB1). Targeting these resistance mechanisms using different strategies has led to various levels of success in overcoming resistance to current therapies. For instance, targeting AR-V7 with niclosamide or AKR1C3 with indomethacin can improve enzalutamide and abiraterone treatment. ABCB1 transport activity can be inhibited by the dietary constituent apigenin and antiandrogens such as bicalutamide which in turn improves response to docetaxel. A more thorough understanding of how drug resistance develops will lead to improved treatment strategies. This review will cover the current knowledge of resistance mechanisms to castration resistant prostate cancer therapies and methods that have been identified which may improve treatment response. Keywords: Prostate cancer, Castration resistant prostate cancer, Enzalutamide, Abiraterone, Docetaxel, Drug resistance